Peran Undang-Undang Republik Indonesia Nomor 9 Tahun 2013 Tentang Pencegahan dan Pemberantasan Tindak Pidana Pendanaan Terorisme dalam Pemberantasan Terorisme: Tantangan dan Strategi di Era Digital (Postulat, 2023)
Terrorism is a crime against humanity and human civilization and includes a major threat to humanity and human civilization and is also a serious threat to the integrity and sovereignty of a country. In the era of globalization, technological progress is the main factor that triggers the transformation of a lifestyle and system from traditional culture to digital. In addition, globalization has become a renewal capable of accelerating the development of terrorism through new technological literacy that can assist the movement of terrorist organizations. Psychological motivation is a factor that can lead to acts of terrorism. In addition to psychological encouragement, funding is a major factor in carrying out acts of terrorism. Because acts of terrorism are carried out on a large scale, this is a problem that must be borne and overcome by the government. However, in practice, up to now, efforts to prevent and eradicate criminal acts of terrorism still often encounter obstacles. But the hope of eradicating terrorism has not disappeared. In order to protect the sovereignty and security of the Indonesian nation, the government made and ratified the Republic of Indonesia Law No. 9 of 2013 concerning the Prevention and Eradication of Terrorism Financing Crimes. With this law, the Financial Services Authority can make it the basis for efforts to prevent the financing of terrorist crimes, as well as the government working together with the Financial Services Authority, because considering that the economic sector has started to transform into an all-digital, it requires supervision in the latest way.